Effect of Pb(NO3)2 on Preparation and Properties of CF/β-PbO2 Electrodes for Zinc Electrowinning. (12th October 2020) - Liu, Jianhua; Xu, Jian; Han, Zhaohui
Abstract : In this study, the β -PbO2 active layer was deposited on the surface of the carbon fiber cloth by electrodeposition. The CF/ β -PbO2 electrode was investigated by scanning electron microscopy (SEM), anodic polarization curves, Tafel curves, and a four-probe method. It was found that a uniform and flattened dense β -PbO2 active layer is obtained when the concentration of Pb(NO3 )2 is 150 g l −1 . The deposition quality of the active layer of β -PbO2 particles in the carbon fiber is affected by the concentration of Pb(NO3 )2, thereby affecting the interfacial bonding strength between the active layer and the carbon fiber. The weightlessness rate of the carbon fiber substrate electrode materials with Pb(NO3 )2 concentration of 150 g l −1 are the smallest. The interface resistivity of the CF/ β -PbO2 electrode sample with Pb(NO3 )2 concentration of 150 g l −1 is 6.71 × 10 −5 Ω·m and is smallest. The CF/ β -PbO2 electrode prepared under the 150 g l −1 has the smallest oxygen evolution potential and is 2.335 V. When the concentration of Pb(NO3 )2 is 150 g l −1, the prepared CF/ β -PbO2 electrode has the largest corrosion potential (1.085 V) and the minimum corrosion current (2.074 × 10 −4  A · cm −2 ).